2018
DOI: 10.17925/enr.2018.13.1.38
|View full text |Cite
|
Sign up to set email alerts
|

Association Between the ABO Blood Types and Post-operative Pain

Abstract: A number of genetic factors such as gender and hair colour have been associated with pain. ABO blood types have been linked to a diverse range of diseases such as various types of cancer, but only two studies have investigated a possible link between ABO blood types and pain. Thus, the aim of this study was to investigate if an association exists between a certain blood type and post-operative pain. Patients (18–40 years) who had an anterior cruciate ligament (ACL) reconstruction at Aalborg University Hospital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 45 publications
0
15
0
Order By: Relevance
“…However, a study by Shankar et al 18 observed a tendency of blood group B exhibiting a non-significant lowest pain threshold and pain tolerance. In another study done by Lausten et al 25 in patients who had undergone reconstructive knee surgery, there was no significant difference between post-operative pain measured by the amount of postoperative analgesics consumed and blood types A, B and O.…”
Section: Discussionmentioning
confidence: 84%
“…However, a study by Shankar et al 18 observed a tendency of blood group B exhibiting a non-significant lowest pain threshold and pain tolerance. In another study done by Lausten et al 25 in patients who had undergone reconstructive knee surgery, there was no significant difference between post-operative pain measured by the amount of postoperative analgesics consumed and blood types A, B and O.…”
Section: Discussionmentioning
confidence: 84%
“…However, in our study, it was observed that patients with B blood group had similar senseof pain intensity like patients with AB blood group and pain perception severity showed a ranking such as B = AB> O> A in terms of blood groups. Lausten et al investigated the association between postoperative pain and ABO blood type in patients undergoing anterior cruciate ligament reconstruction and no significant difference was found between blood groups and analgesic use, but it was shown that patients with 0 blood type were more likely to use analgesics (24). In another study investigating the effect of blood groups on pain perception, male students kept their dominant hands in 4-6 ° C cold water.…”
Section: Discussionmentioning
confidence: 99%
“…These ABO-mediated changes in membrane topology can explain the several pathophysiologic differences between various blood groups [128]. ABO blood type has been linked to a number of diseases, including cancer and musculoskeletal diseases [92]. For example, blood group A was confirmed by several studies to be associated with elevated risk of gastric cancer, while blood group O with lower risk of pancreatic cancer [129].…”
Section: Glycan Reactionsmentioning
confidence: 99%
“…The ABO blood group is the most important blood group system in transfusion and transplantation medicine [91]. The ABO blood system consists of four blood types (A, B, AB and O) [92]. Three variant alleles (A, B, and O) of a single gene on chromosome 9q34, the ABO gene, determine a person's blood type by encoding two active glycosyltransferases (A and B) with different substrate specificities [93].…”
Section: Food Glycans and Antigensmentioning
confidence: 99%
See 1 more Smart Citation